2021
DOI: 10.1038/s41419-021-04274-7
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation between ER stress and autophagy in renal tubular fibrosis and apoptosis

Abstract: Both endoplasmic reticulum (ER) stress and autophagy have been implicated in chronic kidney injury and renal fibrosis. However, the relationship and regulatory mechanisms between ER stress and autophagy under this condition remain largely unknown. In this study, we first established a mouse model of ER stress-induced chronic kidney injury by 2 weekly injections of a low dose of tunicamycin (TM), a classical ER stress inducer. This model showed the induction of ER stress, autophagy, fibrosis and apoptosis in ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Knockdown of PERK can reduce ERS-mediated autophagy activity and regulation of myocardial fibrosis in H9c2 cardiomyoblasts [44]. A recent study suggested the PERK-eIF2α pathway has a critical role in autophagy activation and fibrotic changes during ER stress in renal tubular cells [45]. In our previous study, we confirmed that inhibiting the expression of ATF4 can promote autophagy in NRK-52E cells, thereby reducing tubular interstitial fibrosis in DN [17].…”
Section: Discussionsupporting
confidence: 77%
“…Knockdown of PERK can reduce ERS-mediated autophagy activity and regulation of myocardial fibrosis in H9c2 cardiomyoblasts [44]. A recent study suggested the PERK-eIF2α pathway has a critical role in autophagy activation and fibrotic changes during ER stress in renal tubular cells [45]. In our previous study, we confirmed that inhibiting the expression of ATF4 can promote autophagy in NRK-52E cells, thereby reducing tubular interstitial fibrosis in DN [17].…”
Section: Discussionsupporting
confidence: 77%
“…Consistently, blockade of autophagy suppressed TGFB1-induced fibrotic changes in cultured renal tubular cells. Furthermore, our recent study demonstrated the reciprocal regulation between endoplasmic reticulum stress and autophagy in chronic kidney injury and fibrosis ( Shu et al, 2021 ). Specifically, autophagy was activated during ER stress and led to renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in maladaptive kidney repair including especially renal fibrosis has been very controversial ( Kim S. et al, 2012 ; Kim W. et al, 2012 ; Bernard et al, 2014 ; Ding et al, 2014 ; Li et al, 2016 ; Livingston et al, 2016 ; Shu et al, 2021 ). In previous work, we characterized the key features of maladaptive kidney repair in mice after RLDC treatment, including persistent inflammation, progressive interstitial fibrosis, “atubular” glomerulus and renal function decline, and further established an in vitro model of RLDC treatment of cultured renal tubular cells ( Fu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress markers such as PERK, ATF6, IRE1‐α and their downstream regulatory genes eIF2α, CHOP, XBP‐1 , regulate autophagy during AKI‐to‐CKD transition (Shu et al, 2021). Shu et al (2021) observed the reciprocal regulation between the ER stress and autophagy in AKI‐to‐CKD transition using the C57BL/6 mice model. On 7th day of tunicamycin administration, C57BL/6 mice showed higher expression of GRP78, PERK, and eIF2α compared to the normal group, demonstrating the activation of the PERK‐eIF2α axis (Figure 3).…”
Section: Crosstalk Between Er Stress and Autophagy In Aki Aki‐to‐ckd ...mentioning
confidence: 99%
“…On 7th day of tunicamycin administration, C57BL/6 mice showed higher expression of GRP78, PERK, and eIF2α compared to the normal group, demonstrating the activation of the PERK‐eIF2α axis (Figure 3). Moreover, the activation of autophagy occurs after the 7th day of tunicamycin administration (Shu et al, 2021). After 14th day, overexpression of the fibrotic markers‐fibronectin, collagen was observed, indicating interstitial fibrosis in the same animals.…”
Section: Crosstalk Between Er Stress and Autophagy In Aki Aki‐to‐ckd ...mentioning
confidence: 99%